MR Angiography of the Great Anterior Radiculomedullary Artery (Adamkiewicz Artery) Validated by Digital Subtraction Angiography - Nijenhuis, R.J.; Mull, M.; Wilmink, J.T.; Thron, A.K.; Backes, W.H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Imaging of the anterior superficial spinal cord arteries by MR angiography is hindered by their small calibers and the similarity in configuration with the anterior superficial spinal cord veins. To validate the location and spatial configuration of the great anterior radiculomedullary artery, (ie, the Adamkiewicz artery [AKA]), contrast-enhanced MR angiography (CE-MRA) was compared with digital subtraction angiography (DSA).METHODS: Fifteen patients with suspected spinal cord vascular pathology underwent both spinal CE-MRA and selective spinal DSA. Two phase CE-MRA was performed with the use of a centric k-space filling scheme synchronized to the contrast bolus arrival. The level and side of the AKA origin were scored on the DSA and CE-MRA images and compared regarding image quality in terms of vessel conspicuity, contrast, continuity, sharpness, and background homogeneity on a relative 5-point scale.RESULTS: Localization and spatial configuration of the AKA by CE-MRA was in agreement with DSA findings in 14 of 15 cases. One mismatch of 1 vertebral level (not side) appeared as a result of the tangled vascular pathology. Comparison of image quality revealed that DSA is superior to CE-MRA concerning vessel continuity, sharpness, and background homogeneity (P < .001). Overall vessel conspicuity and contrast were judged to be similar.CONCLUSION: CE-MRA can visualize and localize the level of the AKA correctly. Image quality of CE-MRA is sufficient for detection of the AKA but is inferior to DSA.